Crosstalk between Sertoli and Germ Cells in Male Fertility. Issue 2 (February 2020) - Wu, Siwen; Yan, Ming; Ge, Renshan; Cheng, C. Yan
Abstract : Spermatogenesis is supported by intricate crosstalk between Sertoli cells and germ cells including spermatogonia, spermatocytes, haploid spermatids, and spermatozoa, which takes place in the epithelium of seminiferous tubules. Sertoli cells, also known as 'mother' or 'nurse' cells, provide nutrients, paracrine factors, cytokines, and other biomolecules to support germ cell development. Sertoli cells facilitate the generation of several biologically active peptides, which include F5-, noncollagenous 1 (NC1)-, and laminin globular (LG)3/4/5-peptide, to modulate cellular events across the epithelium. Here, we critically evaluate the involvement of these peptides in facilitating crosstalk between Sertoli and germ cells to support spermatogenesis and thus fertility. Modulating or mimicking the activity of F5-, NC1-, and LG3/4/5-peptide could be used to enhance the transport across the blood–testis barrier (BTB) of contraceptive drugs or to treat male infertility. Highlights: The testis produces three endogenous regulatory bioactive peptides known as F5-, NC1-, and LG3/4/5-peptide to modulate blood–testis barrier (BTB) and spermatogenic functions. F5- and NC1-peptide promote BTB remodeling by making the barrier 'leaky' and facilitate the degeneration of adhesion sites at the Sertoli–spermatid interface known as the apical ectoplasmic specialization (ES), to support the transport of preleptotene spermatocytes across the immunological barrier and the release of sperm at spermiation. LG3/4/5-peptide, however, promotes BTB function by making the barrier 'tighter', and promotes spermatid adhesion in the testis. These three bioactive peptides thus serve as molecular switches that can turn various cellular events 'on' or 'off' during the epithelial cycle of spermatogenesis.